Bond behaviour and durability of FRP composites applied externally to masonry structures - Oliveira, Daniel V. (2014)
The several advantages associated to the use of FRP composites for civil structural applications (mainly reinforced concrete and masonry) has led to a considerable increment in use during the last years. However, the performance of FRP composite strengthening systems when exposed to harsh environmental conditions is a matter of great concern, which justifies the recent research efforts towards the characterization of the deterioration effects. This paper discusses some of the most relevant environmental agents and their effect on the durability of FRP-strengthened concrete and masonry constructions. The results of a comprehensive series of accelerated ageing tests (water immersion and hygrothermal exposure) on external GFRP-strengthened masonry and respective constituent materials recently carried out at University of Minho are presented and discussed in detail.